"A Drop in the Ocean": A Reflection on the Application of Cognitive Analytic Therapy Within a Prison Setting. Issue 3 (July 2018) - Roper, Louise
Abstract : ABSTRACT: This article reflects on the application of cognitive analytic therapy (CAT) with prisoners referred to a mental health in-reach team within a U.K. prison based on the author's experience as a clinical psychologist. The extent of mental health problems in the prison population and the provision of mental health services within prisons are summarized to highlight the extent of mental health need within this setting. The central concepts and tools of CAT that provided the framework within which this author's work was undertaken within the prison are detailed, namely, reciprocal roles and reciprocal role procedures. Personal reflections on the utility of CAT within a prison setting are presented, including how CAT informed understanding of risk. The application of CAT to the role of forensic nurses within mental health in-reach teams is also considered.